Cognitive Behaviors in Indonesia- English Translation: Exploring Translation Processes - Tatu Zakiyatun Nufus (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2022)
Cognitive development which emerged in Europe in 18century was concerned with the nature of knowledge and with structures and processes by which it was acquired. The research is a qualitative study that investigates translation cognitive behavior in Indonesian – English text which explored the translation process of Indonesian text. This research used descriptive analysis to interpret the data. The data source is recording video or transcription data that run between a female student and her professor in getting meaning of the word in good translation using many strategies in finding appropriate meaning. Cognitive behaviors show all mental processes which people use on daily basis such as memory, learning, problem-solving, evaluation, and decision making, these activities can help the translator to generate ideas in identifying difficult words from the source text to target language.